Analisis Faktor-Faktor yang Mempengaruhi Kinerja Perawat - Okwerita Okwerita; Yulihasri Yulihasri; Zifriyanthi Minanda Putri (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between room head empathy, cohesiveness, and job satisfaction with the performance of implementing nurses at Sungai Dareh Regional Hospital, Dharmasraya Regency. The method used is descriptive quantitative with a cross-sectional method. The research results show that each variable influences the performance of executive nurses with a p-value of 0.000 for empathy, 0.001 for cohesiveness, and 0.000 for job satisfaction with a medium-strength relationship. In conclusion, the higher the vacancy of the head of the room, the cohesiveness and job satisfaction of nurses, the more the performance of implementing nurses at Sungai Dareh Regional Hospital will improve. Keywords: Empathy, Job Satisfaction, Nurse Performance, Cohesiveness